Space RADSIM: Binary-Agnostic Fault Injection to Evaluate Cosmic Radiation Impact on Exploit Mitigation Techniques in Space - Willbold, Johannes; Cloosters, Tobias; Worner, Simon; Buchmann, Felix; Schloegel, Moritz; Davi, Lucas; Holz, Thorsten (Proceedings - IEEE Symposium on Security and Privacy, 2025)
Over the past decade, the proliferation of Low Earth Orbit satellites, driven by lower launch costs, has revolutionized space applications, from communication to earth observation and weather forecasting. This trend also introduced a shift in hardware: Specialized radiation-resistant hardware was displaced by cheaper commercial off-the-shelf components. As a critical part of modern infrastructure, satellites attract cyber attacks and are subject to terrestrial and space-specific threats, necessitating effective security measures. However, cryptographic protections and exploit mitigations remain limited in productive satellite firmware. Academic research on satellite security only focuses on cryptographic protections, which raises the question if exploit mitigation strategies are suitable for satellites or impacted by space-specific factors, such as cosmic radiation. In this paper, we present the first systematic analysis of 381 small satellite designs, identifying the prevalence of commercial off-the-shelf hardware platforms in space projects and the availability of ready-to-use exploit mitigation strategies for satellite platforms. Since mitigations are seemingly available, we explore the effects of cosmic radiation on software-based exploit mitigations by implementing RADSIM, an automated tool for simulating single event errors (bitflips). Our study simulated over 21 billion faults in differently hardened satellite firmware binaries to assess the fault tolerance of exploit mitigation strategies in the presence of cosmic radiation. Our results reveal that some mitigations barely impact the fault tolerance, while others increase the error probability of hardened satellite firmware by up to 19%. These findings provide novel insights into the tradeoffs between exploit mitigation effectiveness and radiation resilience, offering guidance to satellite developers on optimizing security in space-based systems.